1998
DOI: 10.1016/s0550-3213(98)00327-7
|View full text |Cite
|
Sign up to set email alerts
|

The Higgs mass in the MSSM infrared fixed point scenario

Abstract: In the infrared fixed point (IFP) scenario of the minimal supersymmetric model (MSSM), the top-quark mass and other physical quantities of the low-energy theory are insensitive to the values of the parameters of the theory at some high energy scale. In this framework we evaluate the light CP-even Higgs mass, m h 0 , taking into account some important effects that had not been previously considered. In particular, the supersymmetric correction to the relation between the running and the physical top-quark masse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 71 publications
1
49
0
Order By: Relevance
“…A reduction of the number of independent parameters in the infrared quasi-fixed point regime made it possible to determine, to a sufficiently high degree of precision, an upper limit on the mass of the lightest CP-even Higgs boson. In the case being considered, comparatively small values of tan β result in that its mass does not exceed 94 ± 5 GeV [11]- [13]. This limit is 25 − 30 GeV lower than the absolute upper limit in the minimal SUSY model.…”
Section: Introductionmentioning
confidence: 82%
“…A reduction of the number of independent parameters in the infrared quasi-fixed point regime made it possible to determine, to a sufficiently high degree of precision, an upper limit on the mass of the lightest CP-even Higgs boson. In the case being considered, comparatively small values of tan β result in that its mass does not exceed 94 ± 5 GeV [11]- [13]. This limit is 25 − 30 GeV lower than the absolute upper limit in the minimal SUSY model.…”
Section: Introductionmentioning
confidence: 82%
“…These comparatively small values of tan β lead to much more stringent constraints on the mass of the lightest Higgs boson. A detailed theoretical analysis performed in [3], [4], revealed that, in the case being considered, its mass does not exceed 94 ± 5 GeV, which is 25 − 30 GeV below the absolute upper limit in the minimal SUSY model. It should be noted that the LEP II constraints on the mass of the lightest Higgs boson [6] are such that a considerable fraction of solutions approaching a quasi-fixed point at tan β ∼ 1 have already been ruled out by existing experimental data.…”
Section: Introductionmentioning
confidence: 89%
“…Since µ eff , B 0 , and y have been found we investigate the dependence of the Higgs boson spectrum on A, m 0 , and µ ′ using the relations (16). For the masses of CP-odd states one can get an exact analytical result:…”
Section: The Procedures Of the Analysismentioning
confidence: 99%
“…It has been shown that in the vicinity of this point the b − τ Yukawa coupling unification is realised [13]. In the recent publications (see [15][16][17]) the value of tan β that corresponds to quasi-fixed point regime has been calculated. It is restricted between 1.3 and 1.8.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation